2017
DOI: 10.1590/1518-8345.2190.2951
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two bundles on central catheter-related bloodstream infection in critically ill patients

Abstract: Objective:To evaluate the impact of the implementation of insertion and maintenance bundles on the rates of catheter-related bloodstream infection in an intensive care unit. Method:This is a quasi-experimental, before-and-after study with a non-equivalent control group. During a six-month period, insertion and maintenance bundles for the central venous catheters were implemented. Supervision guidelines were developed to assess compliance with the bundle and catheter characteristics. Results:A total of 444 cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
(39 reference statements)
2
5
0
6
Order By: Relevance
“…Regarding the overall incidence density of the PBSI, a study that evaluated the implementation of bundles to control CVC-related infections showed a reduction in the incidence of bloodstream infections from 2.4% to 0.9% in the pre-and post-intervention periods, respectively (21) , corroborating with the results of this research.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the overall incidence density of the PBSI, a study that evaluated the implementation of bundles to control CVC-related infections showed a reduction in the incidence of bloodstream infections from 2.4% to 0.9% in the pre-and post-intervention periods, respectively (21) , corroborating with the results of this research.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the hand hygiene component, an observational research evidenced the execution of this practice in only 10.7% of the observations made (16) , which brings conflicting results with this study, in which this practice was verified in 100% of the cases. It is understood that hand hygiene is one of the most important measures to prevent infections, guaranteeing a safe care for both patients and health professionals, as shown in a study (21) , which obtained a reduction in the infection rate from 7.8 to 2.3 episodes/1,000 CVC per day.…”
Section: Resultsmentioning
confidence: 98%
“…[10] A study that investigated the impact of bundles to reduce sepsis in the ICU showed a significant reduction in the rate of central catheter-related bloodstream infection. [11] Similarly, decreased rates of CAUTI and VAP have been reported in the ICU after the implementation of the respective bundles. [12,13] Overall, the implementation of the various bundles appears to have contributed significantly to reducing the incidence of sepsis in the ICU, especially with regard to resistant bacteria such as A. baumannii, and helps to decrease the spread of infection among ICU patients.…”
Section: Discussionmentioning
confidence: 86%
“…A systematic approach on a daily basis using daily goals sheet, nurse-driven protocols, electronic reminders, or multidisciplinary catheter rounds are possible interventions [6]. The simultaneous implementation of insertion and maintenance bundles has a positive impact on the reduction of catheter-related bloodstream infection [7].…”
Section: Introductionmentioning
confidence: 99%